Two-Dimensional Material-Based Colorimetric Biosensors: A Review - Danzhu Zhu; Bin Liu; Gang Wei (Biosensors, 2021)
Two-dimensional (2D) materials such as graphene, graphene oxide, transition metal oxide, MXene and others have shown high potential for the design and fabrication of various sensors and biosensors due to their 2D layered structure and unique properties. Compared to traditional fluorescent, electrochemical, and electrical biosensors, colorimetric biosensors exhibit several advantages including naked-eye determination, low cost, quick response, and easy fabrication. In this review, we present recent advances in the design, fabrication, and applications of 2D material-based high-performance colorimetric biosensors. Potential colorimetric sensing mechanisms and optimal material selection as well as sensor fabrication are introduced in brief. In addition, colorimetric biosensors based on different 2D materials such as graphene, transition metal dichalcogenide/oxide, MXenes, metal–organic frameworks, and metal nanoplates for the sensitive detection of DNA, proteins, viruses, small molecules, metallic ions, and others are presented and discussed in detail. This work will be helpful for readers to understand the knowledge of 2D material modification, nanozymes, and the synthesis of hybrid materials; meanwhile, it could be valuable to promote the design, fabrication, and applications of 2D material-based sensors and biosensors in quick bioanalysis and disease diagnostics.